Harlequin Syndrome after Thoracoscopic Repair of a Child with Tracheoesophageal Fistula (TEF) - Richard Wagner (European Journal of Pediatric Surgery Reports, 2019)
Harlequin syndrome (HS) is a rare dysautonomia of the sympathetic nervous system leading to asymmetric facial flushing and sweating. In the literature, only a few cases of HS after thoracoscopic tracheoesophageal fistula (TEF) repair are reported. We report on a newborn with TEF who developed HS after thoracoscopic repair. On the first day of life, the girl (3,480 g, gestation age: 41 week) underwent thoracoscopic repair of a type C esophageal atresia (TEF; OR time 105 minute) without complications. The postoperative course was uneventful, the patient swallowed and thrived well and did not require esophageal dilatations. At 2 years of age, missing facial flushing, transpiration, and warming on the right side of her face during agitation were noticed. As no further intervention was required, the girl and her parents adapted well to the symptoms. Our report shows that the late onset of HS after the surgical procedure is unlikely a direct causal relation to the thoracoscopic operation but rather a shared embryological pathogenesis, like a neurocristopathy.